Cacos de cerâmica e fazendas camponesas : o campesinato itálico nas categorias de classificação de sítios nos levantamentos de superfície - Knust, José ([Actas])
Roman peasant studies have widely used data produced by central Italian field survey's projects in last decades. This procedure is tributary of the classification scheme used to interpret these archaeological remains, mainly based in the categories 'Villa' and 'Small Farm'. Both are determined by a pre established debate on the crises of Roman peasantry and rise of 'slave-run villa', as well preconceived images of what is a 'slave-run estate' and a "peasant farm". In this paper, I want to raise some questions about what I consider the basic assumptions driving the image of a 'peasant farm', which underlies this interpretation scheme. I believe this image is fundamentally linked to a traditional and out-of-date idea on what is a peasant - which had been seen as a backward social group, isolated, and solely concerned on the production of its subsistence. We can criticize it theoretically, from categories' perspective, as well empirically, from the perspective of some recent excavations of archaeological sites probably linked to the Italic peasantry